Malacofaunas de las Formaciones Paraná y Puerto Madryn (Mioceno marino, Argentina): su origen, composición y significado bioestratigráfico - del Río, Claudia Julia
The Middle- lower Late Miocene sea that covered the eastern part of Argentina, deposited an interesting fossiliferous sequence dominated by molluscs. These horizons comprise the Puerto Madryn Formation that crops out in northeastern Patagonia, the Paraná Formation exposed along the Paraná River (Entre Ríos Province), and thestrata placed in the subsurface of the Buenos Aires Province. The most conspicuous feature of each one of these units is the abundant, diverse and exceptionally well preserved molluscan assemblages contained in thick shell-beds recovered throughout the sequence. Its homogenous stratigraphic distribution and distinctive composition allowed the Aequipecten paranensisZone and the Aonikense Molluscan Stage to be recognized in northeastern Patagonia (Del Río,1988). Because of the compositional similarities among assemblages from Patagonia and those contained in the Paraná Formation and in the subsurface of the Buenos Aires Province, it is proposed to extend the Aequipecten paranensis Zone to include faunas yielded in the latter units. The lower “Paranense Stage”, the “Entrerriense Stage” and the uppermost marine“Rionegrense Stage” of the Paraná Formation contain the same molluscan assemblage and this fact does not support the idea these stages to represent three different transgresions as it was previously thought. Composition of this fauna indicates that deposition varied from mid-shelf to intertidal environments and also points to the development of tropical temperatures in Southwestern Atlantic Ocean during Middle-lower Late Miocene times, before the abrupt cooling recorded in Antartic and Subantartic waters by 10 MA ago. Its taxonomic composition reveals the extinction of most paleoaustral elements that had characterized the Southern Hemisphere Paleogene faunas, as well as the abrupt increase of Caribbean-Indo-Pacific taxa, an extremely poor represented group in the oldest Patagonian assemblages, and also shows the strong development of endemic elements of the American continent. Fil: del ...